Gambaran Kemampuan Interaksi Sosial dan Turn Taking pada Anak Prasekolah - Meisya Weldiani; Ari Sarwanto; Alfiani Vivi Sutanto (Politeknik Kesehatan Kemenkes Surakarta, 2022)
Abstract Background: The ability of preschool children to interact socially with their friends requires good communication skills. Communicating verbally requires mature language skills in terms of phonology, semantics, morphology, syntax and pragmatics. When preschool children interact with their friends using verbal communication, of course, each of them should take turns conveying messages verbally. Turn-taking skills between two or more preschool children and preschool children with the people around them will continue to develop their abilities by frequently carrying out social interactions that they build. The more often and skillfully preschool children carry out social interactions with other people around them, of course, the better their turn-taking skills will be. Therefore, parents and families need to frequently train their children's social interaction and turn-taking skills.. Objectives: This study aims to determine the description of social interaction and turn-taking skills in preschool children. Methods: This study is a quantitative study with a descriptive approach. The sample in this study was 30 preschool children with a sampling technique using a purposive sampling technique. The statistical test used in this study used the Spearman's rank test.. Results: The results of the Spearman's rank test obtained Sig.0.007 with a Correlation Coefficient / r value of 0.480 accepting Ha and rejecting Ho, this means that social interaction is related to turn-taking ability in preschool children. Conclusion: There is a relationship between social interaction and turn talking ability in preschool children Keywords : Social Interaction, Turn Taking